Enhanced performance of zinc oxide arrester by simple modification in processing and design - Karim, A.N. Mustafizul; Begum, Shahida (OMICS Publishing Group, 2014)
Reliable performance of a Zinc Oxide surge arrester is highly dependent on its energy absorption capability. This paper presents two simple but promising approaches for enhancement of this property: one with an alternative sintering orientation and the other with the changed geometry of arrester discs to provide higher surface to volume (S/V) ratio. Several sintering orientations including the control (or conventional) process were tried and assessed. Some of these attempts have demonstrated quite superior results which might be linked to lower level of contamination during sintering. Study conducted to observe the effect of the higher surface to volume (S/V) ratio through geometrical modification of the discs from cylindrical to hexagonal shape has also demonstrated improved outcome. Average energy absorption capability for the hexagonal discs was found to increase markedly which might be attributable to faster heat dissipation aided by higher S/V ratio preventing the discs from premature failure. Thus by combining the appropriate sintering orientation and the change in geometrical shape for higher (S/V) ratio, substantial enhancement of the arrester block capability is achievable which would be eventually helpful for improved protection of electrical system.